How do you solve -3( x + 5) = x - 9+ 2( 5x + 2)?

1 Answer
Sep 25, 2017

x=-5/7

Explanation:

First, we will look at the left side, which is -3(x+5)
We will distribute parentheses/brackets with this:

x(y+z)=xy+xz
Therefore, -3(x+5) is the same as -3*xcancel(+)-3*5

-3*5=-15 so the equation will now be -3x-15.

Let's focus on the right side now.

x-9+2(5x+2)

We'll do the same thing as above, distribute parentheses using:
x(y+z)=xy+xz.

Therefore, 2(5x+2)=2*5x+2*2 which is the same as 10x+4
Now, we put back the x-9+

Equation now:
x-9+10x+4
We first group like terms:
x+10x+4-9
Then add:
11x+4-9
Then subtract:
11x-5

Now we put both sides together to get
-3x-15=11x-5

Add 15 to both sides:
-3x-15color(blue)+color(blue)15=11x-5color(blue)+color(blue)15
Simplify:
-3x=11x+10

Subtract 11x from both sides:
-3xcolor(blue)-color(blue)11color(blue)x=11x+10color(blue)-color(blue)11color(blue)x

Simplify:
-14x=10

Divide both sides by -14

(-14x)/(-14)=10/-14

to get:

x=-5/7